A Proposal for a Low-Cost Educational Digital Twin with Real-Time Web Interface - Lago, Maria E. F.; Oliveira, Daniel F. G. de; Dantas, Rummenige R. (Anais Estendidos do Simpósio de Realidade Virtual e Aumentada (SVR); 2025: Anais Estendidos do XXVII Simpósio de Realidade Virtual e AumentadaDO - 10.5753/svr_estendido.2025.15312, 2025)
This paper presents a proposal for the development of a low-cost educational digital twin for the URA robot, featuring a real-time web interface. The initiative aims to democratize access to interactive technologies in STEM education, promoting practical learning through the integration of hardware, software, and digital simulation. The platform is expected to contribute to student engagement in investigative activities, promoting skills such as critical thinking and autonomy. This article describes the project’s motivations, architecture, and current results, which include a functional prototype of the robot, a web visualization platform, and a defined communication architecture using MQTT. Finally, it presents the next steps for integration and practical validation.